Born of defiance [compact disc, unabridged] - Kenyon, Sherrilyn, 1965- (Kenyon, Sherrilyn, 1965- League., 2015)
Born an Outcast, Talyn Batur has spent the whole of his life fighting against the prejudice of his people. An Andarion without a father is not something anyone wants to be. But when his companion's brother draws him into a plot against the Andarion crown, he finds himself torn between the loyalty to the planetary government that his mother has beaten into him and his own beliefs of justice and right.